Medicinal Plants in the Treatment of Colitis: Evidence from Preclinical Studies - Santana, Marília T.; Cercato, Luana M.; Oliveira, Janaíne P.; Camargo, Enilton A. (Planta Medica, 2017)
Ulcerative colitis is a chronic inflammatory condition whose treatment includes aminosalicylates, corticosteroids, and immunomodulators. Medicinal plants seem to be an important alternative treatment for this condition. They have been the subject of a great number of studies in recent years. This study was conducted to systematically review the medicinal plants tested in experimental models of ulcerative colitis. We conducted a systematic literature search through specialized databases (PUBMED, SCOPUS, EMBASE, MEDLINE, LILACS, SCIELO, and SCISEARCH) and selected articles published between January 2000 and June 21, 2016 by using “medicinal plants” and “ulcerative colitis” as key words. Sixty-eight studies were included, and the families Asteraceae and Lamiaceae presented the largest number of studies, but plants from several other families were cited; many of them have shown good results in experimental animals. However, only a few species (such as Andrographis paniculata and Punica granatum) have undergone clinical tests against ulcerative colitis, and the observation that many preclinical studies reviewed are purely descriptive has certainly contributed to this fact. Chemical constituents (mainly flavonoids and terpenes) seem to play a role in the effects of the plants. Thus, the data herein reviewed reinforce the potential of medicinal plants as a source of alternative approaches to the treatment of ulcerative colitis.
Keywords: ulcerative colitis; medicinal plant; phytotherapy; flavonoid; terpene